In-situ burning for oil spill countermeasures - Fingas, Merv; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
In-situ burning is recognized as a viable alternative for cleaning up oil spills on land and water. It can rapidly reduce the volume of spilled oil and eliminate the need to collect, store, transport, and dispose of recovered oil, and can also shorten the response time to a spill, thus reducing the chances that the spill will spread on the water surface or further into land. This book will serve as a comprehensive reference for all aspects of in-situ burning of oil spills and include the scientific aspects of the burning process and the related effects, as well as practical information about the procedures to be followed and equipment required for carrying out an in-situ burn.
chapter 1 In-Situ Burning: An Update -- chapter 2 Burning on Land and Wetlands -- chapter 3 In-Situ Burning on Ice, Snow or in the Arctic -- chapter 4 In-Situ Burning Operations during the Deepwater Horizon Spill -- chapter 5 The Newfoundland Offshore Burn Experiment -- chapter 6 The Fate of Polycyclic Aromatic Hydrocarbons Resulting from In-Situ Oil Burns.
Keywords: Fuel; Waterworks; TECHNOLOGY & ENGINEERING -- Environmental -- General; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / Water Supply; Environmental Monitoring, Environmental Risk, Environmental Analysis; Ignition Devices, Helitorches; Organic Compounds, Polyaromatic Hydrocarbons, Carbonyls, Dioxins, Dibenzofurans, Btex; Vocs, Carbon Monoxide, Sulphur Dioxide; Water Pollution, Soil Pollution; In situ burning (Oil spill management); In situ remediation; Oil spills -- Cleanup